The role of self-care in perceptions of satisfaction with life, organisational job satisfaction, and self-efficacy in zoo and aquarium professionals - Brando, Sabrina; Goulart, Vinícius Donisete Lima Rodrigues; Buchanan-Smith, Hannah M.; Planellas, Sonia Rey; Caes, Line (Frontiers in Veterinary Science, 2025)
This research sheds light on how professionals with different roles in zoos and aquariums perceive individual and organisational job satisfaction, self-efficacy, and satisfaction with life, and which types of self-care contribute to these variables. This was achieved through a mixed methods approach of a survey (completed by 442 participants) and follow-up interviews (in 39 participants) with recruitment across 23 organisations. For the single question, I am satisfied with my job (reflecting individual job satisfaction), 44% of participants responded somewhat agree and 27% responded strongly agree, indicating that most participants (71%, n = 442) were satisfied with their job, and this was particularly true for those who considered their job a calling. Differences across job roles were found, with the largest variability for those in Junior animal caregiver positions, and with CEOs reporting the highest median of individual job satisfaction scores. A very weak positive significant relationship exists between self-efficacy and levels of organisational job satisfaction, which may be explained by the fact that this relationship is complex and multifaceted. A weak positive significant relationship between self-efficacy and satisfaction with life and a moderate positive relationship between organisational job satisfaction and satisfaction with life were also identified. The Generalised Linear Model analyses revealed that only one factor, Experience, and contributed to all independent variables (i.e., total satisfaction with life, mean organisational job satisfaction, and total self-efficacy), suggesting that participants with more time in the field reported higher total satisfaction with life, organisational job satisfaction, and levels of total self-efficacy. Various types of self-care (physical, emotional, spiritual, and workplace) were also significant positive contributors to satisfaction with life, but only workplace self-care contributed positively to organisational job satisfaction, whereas only intellectual self-care contributed positively to self-efficacy. Thematic analyses of the interview data contextualised the findings, with specific examples. This study contributes important empirical data that provides guidance for developing holistic employee wellbeing programs, continued professional development, and more appropriately aligned education to improve overall wellbeing of zoo and aquarium personnel.